P-110 Embedding a quality and safety approach to a statewide end of life (EOL) program. (1st September 2015) - King, Bernadette; Walker, Amanda
Abstract : Background: The Clinical Excellence Commission's (CEC's) EOL program was established in 2013 in order to support provision of safe, quality end of life care in NSW public health organisations (PHOs). Aim: To ensure all patients who die in NSW hospitals benefit from a safe, consistent approach to individualised end of life care. Methods: Four priority areas have been identified: 1. A standardised death screening tool where EOL care is measured for all patients who die in NSW hospitals 2. The introduction of the AMBER care bundle, a systematic approach which allows patients to receive active treatment alongside an end of life care planning approach. 3. Development of a 'last days of life toolkit' to ensure all patients receive symptom control, have social, spiritual and cultural needs addressed, and bereavement support for families and carers. 4. SHAPE Conversations: (Supporting Health Professionals in Advance Planning and End of Life Conversations) a joint project with NSW Health lead agencies to educate and mentor clinicians in difficult conversations at the EOL. Results: The death screening tool has been implemented statewide. The AMBER care bundle is available to appropriate units where end of life issues could be improved. A Care of the Dying Observation Chart is being piloted. The chart ensures that dying patients are monitored for symptoms and family distress triggering appropriate intervention. Discussion/conclusion: The CEC End of Life program will play an important role in the introduction of a coordinated whole of system approach to EOL care.